Pengaruh Indeks Kemudahan Berbisnis, Foreign Direct Invesment, dan Populasi Penduduk Terhadap Perekonomian ASEAN - Theodoris, Daniel; Wiwin Setyari, Ni Putu; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Economic growth is considered as an indicator to assess whether the economy is doing well or not and to see the total revenue obtained in the economy. This study aimed to analyze the effect of ease of doing business index, foreign direct investment, and the population on the economy of ASEAN. The data used in this research is secondary data in the form of ease of doing business index, foreign direct investment, and the population of ASEAN with a period of 2010-2015. The technique of analyzing data use Fixed Effect Method (FEM) as the best panel model. Based on test results, simultaneously found that the three independent variables have a significant influence to GDP of ASEAN, while partially the ease of doing business index, foreign direct investment, and the population had a significant positive impact to GDP of ASEAN. The population turned out to be relatively the most influential to GDP of ASEAN compared to the ease of doing business index and foreign direct investment (FDI).